Turkey and Europe’s Place In International Trade Logistics - Kişman, Zülfükar Aytaç; Aydın, Fatma (Taner NAMLI, 2020)
International trade is a concept that has gained importance in the context of the relations of countries with each other, and has gained importance in the aftermath of World War II as a concept that increases in parallel with the political relations of the countries and contributes to the development of political relations. Due to the importance of international trade, various arrangements are made by international organizations in order to ensure that trade relations between countries take place correctly and smoothly. The logistics sector, which can be expressed as the veins of international trade, is one of the popular business areas of the future and has been developing in recent years. Companies give great importance to this sector both in order to ensure their superiority in the competitive environment and to ensure their continuity. The share of countries in the logistics sector is also getting important day by day. The purpose of this study is an overview of logistics industry and giving general information on logistics operations, and is to try to understand Turkey's place in this sector.

Uluslararası ticaret ülkelerin birbirleriyle olan ilişkileri bağlamında gün geçtikçe etkisi artan ve ülkelerin politik ilişkileri ile paralellik arz eden ve politik ilişkilerin de gelişmesine katkıda bulunan bir kavram olarak özellikle 2. Dünya Savaşı sonrasında önem kazanarak karşımıza çıkmaktadır. Uluslararası ticaretin önemine binaen ülkeler arasındaki bu ticari ilişkilerin doğru ve sorunsuz şekilde yürümesi için de çeşitli düzenlemeler uluslararası kuruluşlarca yapılmaktadır. Uluslararası ticaretin damarları olarak ifade edilebilecek olan lojistik sektörü ise geleceğin gözde iş alanlarından biri olarak son yıllarda gelişen bir sektördür. Firmalar gerek rekabet ortamında mevcut üstünlüğünü sağlayabilmek için gerekse de sürekliliklerini temin etmek için bu sektöre oldukça önem vermektedirler. Ülkelerin lojistik sektörü içerisinde aldıkları pay da hakeza gün geçtikçe önem arz etmektedir. Bu çalışmanın amacı lojistik sektörüne genel bir bakış ile beraber lojistik operasyonlar hakkında bilgi verip Türkiye’nin bu sektör içindeki yerini anlamaya çalışmaktır.
Uluslararası Ticaret Lojistiğinde Türkiye ve Avrupa’nın Yeri